2011
DOI: 10.1177/0963721411422522
|View full text |Cite
|
Sign up to set email alerts
|

Context in Emotion Perception

Abstract: We review recent work demonstrating consistent context effects during emotion perception. Visual scenes, voices, bodies, other faces, cultural orientation, and even words shape how emotion is perceived in a face, calling into question the still-common assumption that the emotional state of a person is written on and can be read from the face like words on a page. Incorporating context during emotion perception a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

35
486
1
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 737 publications
(577 citation statements)
references
References 22 publications
35
486
1
7
Order By: Relevance
“…However, for older children and adults occluding the mouth significantly impairs performance. This is consistent with an emergent ability to change strategies when processing faces for emotion or identity, taking account of different contextual factors for each type of judgment (Barrett, Mesquita, & Gendron, 2011).…”
Section: Resultsmentioning
confidence: 65%
“…However, for older children and adults occluding the mouth significantly impairs performance. This is consistent with an emergent ability to change strategies when processing faces for emotion or identity, taking account of different contextual factors for each type of judgment (Barrett, Mesquita, & Gendron, 2011).…”
Section: Resultsmentioning
confidence: 65%
“…ratings of facial expressions, Hsu and Yang, 2013;Marian and Shimamura, 2013), and are generally referred to as 'contrast effects' (Plous, 1993;Saks et al, 2003;Page et al, 2012). Recent reviews of this literature argue that such effects are not an obstacle to the judgement of discrete emotional states so much as an intrinsic feature of the fluid, dynamic nature of emotion perception (Aviezer et al, 2008;Barrett et al, 2011). A key factor to consider in this light is that the VAS scales used for QBA assessment (and for other health and All respondents (n = 18 'no explanation' and n = 11 'explanation' observer groups) indicated that they could tell when a sheep was hungry.…”
Section: Discussionmentioning
confidence: 99%
“…They adjusted the descriptive terms they generated, and/or how they quantified these terms. Such sensitivity to experimental design and verbal instruction can play a constructive role in scientific studies, focusing observers' attention on key aspects of animal expression, sharpening their ability to discriminate expressive cues and improving the relevance of their scores in light of a study's aims (Aviezer et al, 2008;Barrett et al, 2011). However, this sensitivity can also potentially be a source of undesirable variability and bias (Saks et al, 2003) and therefore understanding this aspect of qualitative measures will help with their appropriate application.…”
Section: Discussionmentioning
confidence: 99%
“…It is still unclear why demographic and SES differently shape the SRH of different ethnic groups, and whether this variation is biological or social. [59][60][61][62][63] Ethnic groups differ in biology, as well as historical life experiences, knowledge, SES, values, cognitive styles, [59][60][61][62][63][64][65][66][67][68][69] emotion processing, 70,71 regulation, [64][65][66][67][68][69] and culture, [72][73][74][75][76][77][78][79][80][81][82] all of which can shape our perception of health and illness.…”
Section: Discussionmentioning
confidence: 99%